Secretory Products of the Human GI Tract Microbiome and Their Potential Impact on Alzheimer's Disease (AD): Detection of Lipopolysaccharide (LPS) in AD Hippocampus - Zhao, Yuhai; Jaber, Vivian; Lukiw, Walter J. (Frontiers in Cellular and Infection Microbiology, 2017)
Although the potential contribution of the human gastrointestinal (GI) tract microbiome to human health, aging, and disease is becoming increasingly acknowledged, the molecular mechanics and signaling pathways of just how this is accomplished is not well-understood. Major bacterial species of the GI tract, such as the abundant Gram-negative bacilli Bacteroides fragilis (B. fragilis) and Escherichia coli (E. coli), secrete a remarkably complex array of pro-inflammatory neurotoxins which, when released from the confines of the healthy GI tract, are pathogenic and highly detrimental to the homeostatic function of neurons in the central nervous system (CNS). For the first time here we report the presence of bacterial lipopolysaccharide (LPS) in brain lysates from the hippocampus and superior temporal lobe neocortex of Alzheimer's disease (AD) brains. Mean LPS levels varied from two-fold increases in the neocortex to three-fold increases in the hippocampus, AD over age-matched controls, however some samples from advanced AD hippocampal cases exhibited up to a 26-fold increase in LPS over age-matched controls. This “Perspectives” paper will further highlight some very recent research on GI tract microbiome signaling to the human CNS, and will update current findings that implicate GI tract microbiome-derived LPS as an important internal contributor to inflammatory degeneration in the CNS.